Bigge, Ägypten. Feldforschungskampagne im Januar 2017 - Schäfer, Bernadeta (e-Forschungsberichte des DAI, 2017)
The aim of the first two years stage of the project that is planned to last for four years is to investigate and to document Nubian vernacular architecture and material culture preserved in the two abandoned villages on the island Bigge in Upper Egypt. The fabric of the two settlements originates from the early 20th century and represents one of very few examples which remained after the inundation of the Egyptian part of Nubia by the waters of Lake Nasser in the 1960s. The combined architectural and ethnological approach should enable a thorough understanding of the material frame of life of the island’s rural community.